2018
DOI: 10.1016/j.jddst.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nucleoside-boronic esters hydrophobic pro-drugs: A possible route to improve hydrophilic nucleoside drug loading into polymer nanoparticles

Abstract: Nucleoside analogues are active therapeutic agents for different types of diseases e.g. Cancer and virus infections. However, they are associated with several side effects due to off-target accumulation. Particulate delivery systems such as nanoparticles (NP) may be able to selectively target drug into affected organs and lower or omit off-target accumulation. Hydrophilic nucleoside analogues are poorly incorporated into NP. This work has used boronic compounds to synthesize more hydrophobic biodegradable prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…The polymer was synthesized following a literature protocol ( Abo-zeid et al, 2018a ). Briefly, poly(glycerol-adipate) (PGA) was synthesized by dissolving equal amounts (250 mmol) of glycerol and divinyl-adipate (DVA) in dry tetrahydrofuran (THF, 30 ml) in presence of a catalytic enzyme, novozyme 435 (1.25 g).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The polymer was synthesized following a literature protocol ( Abo-zeid et al, 2018a ). Briefly, poly(glycerol-adipate) (PGA) was synthesized by dissolving equal amounts (250 mmol) of glycerol and divinyl-adipate (DVA) in dry tetrahydrofuran (THF, 30 ml) in presence of a catalytic enzyme, novozyme 435 (1.25 g).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Poly(glycerol adipate) (PGAd) is a polyester obtained from two non-toxic and bio-based monomers, glycerol and adipic acid (AdA) [41], which are both safe and FDA-approved compounds [42]. PGAd is encountered as a linear or a hyperbranched polymer, depending on the catalysis (Scheme 4).…”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…One of the advantages of linear PGAd over PLA and PLGA, which are extensively used in biomedical applications, is the possibility to modify the pendent hydroxyl groups on the polymer backbone with a variety of acyl groups to change the hydrophobicity of the polymer. It is a smart strategy to produce polymers with completely different properties, based on the kind of acyl moieties used [10,42,58,59,62]. The physicochemical properties of the polymer can be adjusted according to the requirements of different drugs (hydrophilic or hydrophobic) allowing various drug incorporations.…”
Section: Hyperbranched Pgadmentioning
confidence: 99%
See 1 more Smart Citation
“…PGA acylation with fatty acids has been intensively investigated both in terms of physical properties, self-assembling in NPs and for delivery of lipophilic and hydrophilic drugs [31,32,33,34]. The variation of both the fatty acid nature (butyrate, octanoate, laurate, stearate, behenate and oleate) and degrees of substitution have been analyzed for their influence on the final polymer amphiphilic balance, affecting NP shape, drug interactions, NP metabolism and cell uptake [33,35,36]. Weiss et al [33] reported that a low substitution of lauric, stearic or behenic acid decreased nanoparticle size relative to unmodified PGA, suggesting interactions of fatty acid chains in the particle core enhanced the packing of particles (Table 1).…”
Section: Modifications Of Pgamentioning
confidence: 99%